1996
DOI: 10.1097/00005768-199607000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Ankle to arm index following maximal exercise in normal subjects and athletes

Abstract: Recent reports have suggested that minor arterial lesions can be responsible for claudication in athletes occurring only during maximal exercise. Ankle to arm index measurements (AAI) prove the arterial origin of this claudication, but little is known about the normal response of AAI to maximal exercise. Therefore, we studied the response of AAI to maximal exercise in trained and untrained normal subjects. AAI and heart rate (HR) were recorded at rest and following maximal exercise on a cycle ergometer in 15 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Differences in exercise protocols or in the population studied can be possible explanations for this difference. A similar paradoxical result was found between trained and untrained subjects (Desvaux et al ., 1996b). Nevertheless, although the ABI decreased more in untrained subjects performing lower workloads, the ABI to HR relationship was comparable in the two groups (Desvaux et al ., 1996b), and the difference found was expected to be due to a difference in the recovery mode between trained and sedentary subjects.…”
Section: Discussionsupporting
confidence: 81%
“…Differences in exercise protocols or in the population studied can be possible explanations for this difference. A similar paradoxical result was found between trained and untrained subjects (Desvaux et al ., 1996b). Nevertheless, although the ABI decreased more in untrained subjects performing lower workloads, the ABI to HR relationship was comparable in the two groups (Desvaux et al ., 1996b), and the difference found was expected to be due to a difference in the recovery mode between trained and sedentary subjects.…”
Section: Discussionsupporting
confidence: 81%
“…Nevertheless, we previously demonstrated that, in a group of comparable age, highly trained competition athletes had a less pronounced reduction of ABI as compared to sedentary subjects, although performing higher workload (Desvaux et al 1996a).…”
Section: Discussionmentioning
confidence: 84%
“…Then, it is of interest to note that no difference was found in height among the three groups. Although various reviews suggest that ASBP should not decrease in normal subjects following moderate exercise such as walking on a treadmill (King et al 1965;Strandness and Bell 1964;Yao 1973;Yao et al 1969), multiple evidences have been provided that ABI may physiologically decrease following intensive exercise in normal young athletes and untrained young subjects 1996a;Taylor and George 2001). Nevertheless, little is known about aging athletes and maximal exercise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations